Cultures of America Italian Americans - Washburne, Carolyn Kott (Marshall Cavendish Corporation, 1995)
Describes Italy and the reasons people left there to immigrate to America, their adaptation to American society, and their customs regarding food, clothing, language, and music
Keywords: Juvenile Nonfiction; Other; People & Places; United States